Makian Dalam Bahasa Indonesia: Studi tentang Bentuk dan Referensinya - I Dewa Putu Wijana (Humaniora, 2004)
This paper aims at describing forms of swearing expressions and their references used in Bahasa Indonesia. Data which are extracted from The Big Indonesian Dictionary (Kamus Besar Bahasa Indonesia), Indonesian comic books, and the writer's intuition as an Infonesian native speaker, indicate that the sweating expressions can take several forms, i.e. words, phrases, and clauses. With regards to their references, the severing expressions mainly refer to mental state or unlucky situation, animals, devils, bad things, parts of human body, kinship terms, sexual activities and professions.